PERANAN PEMBELAJARAN BERBASIS BUDAYA TERHADAP PERKEMBANGAN SIKAP EMPATI PADA ANAK USIA 5-6 TAHUN - Dwiyani Anggraeni; Muhammad Cholid; Putri Ayu Nurkholik (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
Education plays a crucial role in introducing culture to children from an early age and developing cultural insights as part of character building. Observations at Bina Pelita Global Kindergarten revealed that children were less interested in learning Sundanese folk songs because local cultural learning was not yet a focus of learning activities. This condition led to low interest and motivation in Sundanese culture. This study aims to analyze the role of local culture-based learning in developing empathy skills in children aged 5–6 years. Local culture-based learning is designed to help children recognize, understand, develop, and preserve cultural values ​​in their surroundings. Empathy is a child's ability to understand and feel the emotions of others, enabling them to demonstrate concern in everyday life. This study used qualitative methods with data collection techniques such as observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results show that local culture-based learning can improve children's empathy skills. Therefore, teachers and parents need to consistently instill local cultural values ​​as an effort to develop empathy from an early age.